Envolvimento da serotonina no controle respiratório durante o desenvolvimento pós-natal - Rossato, Vivian Biancardi (2017)
Serotonin (5-HT) is a neurotransmitter involved in nervous system development, being an important modulator of respiratory rhythm via activation of diverse receptors on respiratory neurons. Selective serotonin reuptake inhibitors (SSRIs) such as fluoxetine act as antidepressants and are generally prescribed in depression therapy, including to pregnant women. This study investigated the effects of prenatal (E15-21) exposure to fluoxetine on the ventilatory and metabolic responses to 7% CO2 (hypercapnia) and 10% O2 (hypoxia) of male and female rats during postnatal development (P0-82). To this end, osmotic pumps were implanted subcutaneously in pregnant female rats at embryonic day (E) 15 and delivered vehicle (VEH) or fluoxetine (SSRI, 10 mg/Kg/day) during 7 days. Respiratory frequency (fR), tidal volume (Vt), ventilation (Ve ), O2 consumption (''VO2 ) and air convection requirements (Ve/VO2 ratio) of pups from these litters were studied. In P0-2 male rats, the SSRI group showed a lower Vt and a higher fR in room air conditions, whereas female rats of SSRI group showed a lower Vt in normocapnia normoxica and a higher hyperventilation induced by hypercapnia. At P6-8, male SSRI animals presented a higher fR during hypoxia together with a decrease in the number of neurons that express 5-HT in the caudal dorsal raphe (RDC). P6-8 females from ISRS group showed an attenuated fR during hypoxia. No differences were observed between male rats in the VEH and ISRS groups at P12-14 although there was an increase in the number of 5-HT neurons in the RD. SSRI females showed an attenuated hypercapnic ventilatory response. At P24-26, male SSRI animals showed a lower VEin room air conditions, a higher ventilatory response to hypercapnia and to hypoxia, together with an increase in the number of 5-HT neurons in the ROB and a higher density of TH expression in the LC area. P24-26 SSRI females displayed a lower Ve/V O2 due to a higher V O2 in room air conditions and a higher hyperventilation induced by hypercapnia. In P76-82 male rats, the SSRI group hypoventilated in room air conditions during both wakefulness and NREM sleep and showed a higher increase in Vt induced by hypoxia during wakefulness. These animals showed a higher number of 5-HT neurons in the ROB, RPA and an increase in the number of neurons that express TH in the A5 and in the LC rostral area. Finally, at P76-82, female SSRI rats showed a higher fR in room air conditions during both wakefulness and NREM sleep, an attenuated hypercapnic ventilatory response due to an attenuation of fR during NREM sleep; and an attenuated hypoxic ventilatory response during wakefulness. Also, these animals showed a decrease in the number of 5-HT neurons in the RD. Taken together, these data indicate that SSRI exposure during the prenatal period alters the development of the brainstem respiratory network and results in long lasting and sex specific changes in breathing pattern and in the ventilatory responses to respiratory challenges demonstrating that central and/or peripheric chemoreception may be disrupted in these animals.